Effect of catalysts on microstructure, hydrogen storage thermodynamics, and kinetics performance of La5Mg85Ni10 alloy. (20th September 2019) - Li, Zhenyang; Li, Shengli; Yuan, Zeming; Zhang, Yanghuan; Zhang, Jianyuan
Abstract: The effects of the type and amount of transition metal catalyst on the microstructure and hydrogen storage performance of La5 Mg85 Ni10 + x wt.% M ( x = 1, 3, 5, 7; M = TiF3, NbF5, Cr2 O3 ) alloys milled for 10 h have been investigated. The evolution of microstructure and phase of catalyzed alloys in the absorption/desorption process have been characterized by XRD and HRTEM. The results show that the hydrogen storage capacity of the alloy decreases as the catalyst increases. On the one hand, the catalytic effects of different amount of catalyst TiF3 were studied. TiF3 exists in form of MgF2 and TiH2 phases and E a decreases firstly and then increases as the amount of TiF3 increases. When 5 wt.% TiF3 is added, the hydrogen desorption activation energy shows the lowest E a = 45.2 kJ/mol. On the other hand, the catalytic effects of TiF3, Cr2 O3 and NbF5 are compared in detail. It was found that TiF3 has better catalytic effect than Cr2 O3 and NbF5 due to TiF3 nanoparticles can refine the grains better, provide hydrogen diffusion channels and reduce the nucleation driving force of the alloys. Highlights: La5 Mg85 Ni10 + x wt.% M ( x = 1, 3, 5, 7; M = TiF3, NbF5, Cr2 O3 ) alloys were prepared by ball milling. Both the type and amount of transition metal catalyst have been systematic studied. The alloys show a best hydrogen storage kinetics with the amount of catalysts changing. TiF3 has better catalytic effect than Cr2 O3 and NbF5.